Youth Mental Health In Light Of The Story Of Ashab Al-Kahfi: A Thematic And Analytical Study Of Surah Al-Kahf, Verse 13: الصحة النفسية عند الشباب من خلال قصة أصحاب الكهف (دراسة موضوعية وتحليلية للآية 13 من سورة الكهف) - Muhtadin, Ali; Aulia, Dea (ZAD Al-Mufassirin, 2025)
The rapid development of technology has made social issues increasingly complex. Mental disorder, commonly referred to as "mental health," has become one of the growing issues today. Therefore, the author examines the causes of mental illnesses and their solutions among teenagers, referring to the story of Aṣḥāb al-Kahf in Surah Al-Kahf. This study employs a thematic analysis approach to explore issues surrounding adolescents and mental health. The research methodology includes a literature review, collecting and examining various studies relevant to the topic. Subsequently, the collected data is analysed and integrated with diverse interpretive perspectives, drawing from both traditional and modern interpretive sources. This research focuses on verse 13 and emphasises the words "fityatun" (youth), "āmanū" (they believed), and "hudan" (guidance). The author concludes that the components and instruments found in the story of Aṣḥāb al-Kahf can be drawn upon to unravel the issues and solutions to mental health among teenagers. This is based on the age segmentation and background of the story. The purification of faith becomes a central point in resolving these issues.